Responding to Dogs - Andreyev, Julie (Humanimalia, 2017)
This essay explores the author’s significant experiences with canine companions Tom and Sugi, and the day-to-day events that led to interspecies collaborative art productions. The essay asks, can ethics of care be integrated into aesthetic processes with more-than-human others, specifically dogs? The investigation weaves interpersonal relatings and respectful human-canine discussion into an argument for communication ethics. Interspecies communication is explored for its response potential—compassionate action based on sensing and feeling, combined with respect for difference. The essay focuses on the creative processes of EPIC_Tom (2014-16), a performance and installation project carried out with the participation of the dogs. Their vocal and gestural communications are explored using new media forms, and music and sound-making methods, such as deep listening, call and response, and musicking. The project proposes methods that allow for the relinquishment of human-centric authorship for potentials offered by interspecies creativity.